Empowering women entrepreneurs through microfinance - a case of rural Bangladesh / Saida Parvin - Parvin, Saida (Faculty of Business and Management, UiTM Shah Alam, 2017)
Women's empowerment has been at the centre of research focus for many decades. Extant literature examined the process, outcome and various challenges. Some claimed substantial success, while others contradicted with evidence of failure. But the success remains a matter of debate due to lack of empirical evidence of actual empowerment of women around the world. The current study aimed to address this gap by taking a case study method. The study critically evaluates 20 cases carefully sampled to include representatives from the entire country of Bangladesh. The study demonstrates popular beliefs about microfinance often misguide even the borrowers and they start living in a fabricated feeling of empowerment, facing real challenges to achieve true empowerment in their lives. The impact of this finding is twofold; firstly there is a theoretical contribution, where the definition of women's empowerment is proposed to be revisited considering findings from these cases. And lastly, the policy makers at governmental and non-governmental organisations, and multinational donor agencies need to revise their assessment tools for funding.